PELAKSANAAN FUNGSI PENGAWASAN DPRD TERHADAP PENGELOLAAN APBD KABUPATEN LABUHANBATU-SELATAN BERDASARKAN UNDANG-UNDANG NOMOR 9 TAHUN 2015 TENTANG PEMERINTAH DAERAH: Sutan Tanjung - admin, admin (Fakultas Hukum Universitas Islam Jakarta, 2016)
One of the functions of the Regional People's Legislative Assembly is to oversee the management of APBD which is a form of policy interpretation, political commitments and priorities in deciding where regional money should be spent and from which funds should be collected. DPRD Labuhanbatu-Selatan as a formal institution that is officially instituted is the voice of the needs of the people, it becomes very important that the supervision of budget management. In supervising APBD management, the Labuhanbatu-Selatan DPRD requires clear guidelines on mechanisms and procedures regulated by local regulations. This is in accordance with what is implied in the Decree of the Minister of Home Affairs No. 29 of 2002 on About the Guidelines for Management, Accountability and Supervision of Regional Finance as well as the Procedures for the Formulation of Regional Revenue and Expenditure Budget, Implementation of Regional Financial Procedures and Preparation of Regional Revenue and Expenditure Budget Calculations. However, until now the Regional People's Legislative Assembly of Labuhanbatu-Selatan Regency has not yet regulation (Local Regulation) which regulates the guideline of the implementation of the supervisory function on the management of APBD so that in carrying out its supervisory function, the DPRD of Labuhanbatu-Selatan Regency still has obstacles. The scope of this research is to use normative research procedure. The purpose of this research is to know the Implementation of DPRD Oversight Function on Management of Regional Budget and Expenditure (APBD) of Labuhanbatu-Selatan Regency Based on Law Number 9 Year 2015 About Local Government. The research approach used is the approach of legislation and conceptual approach and approach with interview method. This type of legal material consists of primary legal materials, secondary legal materials, and Al-qur'an Hadist. The technique of collecting legal materials used is literature study which is then processed by using the legal material selection system in data processing techniques. The legal material was analyzed and then drawn conclusions and then provided a prescriptive of the results of the study. Based on the results of research that has been obtained, it can be concluded that the implementation of the function of supervision DPRD Labuhanbau-South district of APBD management is still not maximized. This is because there is no regulation that specifically regulates the supervision system on APBD management. ABSTRAK Salah satu fungsi DPRD adalah melakukan pengawasan terhadap pengelolaan APBD yang merupakan wujud penterjemahan kebijakan, komitmen-komitmen politik dan prioritas dalam memutus kemana uang daerah harus dibelanjakan dan dari mana dana yang harus dikumpulkan. DPRD Labuhanbatu-Selatan sebagai lembaga perwakilan rakyat yang terlembagakan secara formal adalah penyuara kebutuhan rakyat, maka menjadi sangat penting adanya pengawasan terhadap pengelolaan anggaran. Dalam melakukan pengawasan terhadap pengelolaan APBD, DPRD Labuhanbatu-Selatan membutuhkan pedoman yang secara jelas mengenai mekanisme dan prosedur yang diatur dengan peraturan daerah. Hal ini sesuai dengan apa yang diisyaratkan dalam Keputusan Menteri Dalam Negeri Nomor 29 Tahun 2002 Tentang Tentang Pedoman Pengurusan, Pertanggungjawaban Dan Pengawasan Keuangan Daerah Serta Tata Cara Penyusunan Anggaran Pendapatan Dan Belanja Daerah, Pelaksanaan Tata Usaha Keuangan Daerah Dan Penyusunan Perhitungan Anggaran Pendapatan Dan Belanja Daerah. Namun hingga saat ini DPRD Kabupaten Labuhanbatu-Selatan belum Perda (Peraturan Daerah) yang mengatur khusus mengenai pedoman pelaksanaan fungsi pengawasan terhadap pengelolaan APBD sehingga dalam menjalankan fungsi pengawasaannya 0DPRD Kabupaten Labuhanbatu-Selatan masih terdapat kendala-kendala. Ruang lingkup penilitian ini adalah menggunakan tata cara penilitian normatif.Tujuan penelitian ini adalah untuk mengetahui Pelaksanaan Fungsi Pengawasan DPRD Terhadap Pengelolaan Anggaran Pendapatan Dan Belanja Daerah (APBD) Kabupaten Labuhanbatu-selatan Berdasarkan Undang-Undang Nomor 9 Tahun 2015 Tentang Pemerintah Daerah. Pendekatan penelitian yang digunakan yaitu pendekatan perundang-undangan dan pendekatan konseptual serta pendekatan dengan metode wawancara. Jenis bahan hukum terdiri dari bahan hukum primer, bahan hukum sekunder, dan Al-qur’an Hadist. Teknik pengumpulan bahan hukum yang digunakan adalah studi kepustakaan yang kemudian diolah dengan menggunakan sistem seleksi bahan hukum dalam teknik pengolahan data. Bahan hukum dianalisis kemudian ditarik kesimpulan dan selanjutnya memberikan preskriptif tentang hasil penelitian. Berdasarkan hasil penelitian yang telah diperoleh, dapat disimpulkan bahwa pelaksanaan fungsi pengawasan DPRD kabupaten Labuhanbau-Selatan terhadap pengelolaan APBD masih belum maksimal. Hal ini dikarenakan belum ada Perda yang mengatur khusus mengenai sistem pengawasan terhadap pengelolaan APBD.